PENGEMBANGAN MEDIA PEMBELAJARAN KANDANG KATA UNTUK PERKEMBANGAN BAHASA ANAK KELOMPOK B DI PAUD MODERN AL-RIFAIE GONDANGLEGI-MALANG - Fitriani, Devi; Yulia, Nikmahtul Khoir Tri (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2024)
The word cage learning media in children's language learning. The aim of the research is to describe the form of word cage media and the results of the development of word cage media in early childhood learning at Al-Rifa'ie Modern PAUD. The research methodology used is Research and Development (RnD) by developing work in the form of products that will be validated by experts and tested on students. Researchers carried out the RnD stages in a structured manner based on the Bord and Gall theory. The research results of the word cage media were made using six playing techniques which included elements of storytelling, metamorphosis of butterflies and chickens, aspects of children's reading and listening, spelling and arranging the letters to form the names of the animals. In the product validation stage, media experts were 95%, material experts in products were 93%, and material experts in learning were 90.8%. The small group trial stage was 60% and the large group trial stage was 82.75%. It was concluded that the word cage media was suitable for use in children's language learning and was multifunctional and could be used as an interesting and enjoyable learning aid for early childhood.